EFFORTS TO IMPROVE MATHEMATICAL CREATIVE THINKING ABILITY OF STUDENTS IN CLASS VIII-A SMP BPK PENABUR HOLIS BANDUNG IN MATERIALS OF GEOMETRY FLAT SIDE OF SOLID FIGURE THROUGH REALISTIC MATHEMATICS EDUCATION APPROACH - Pertiwi, Citra Megiana; Desti, Ratna Maria ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This research aimed to analyze the role of Realistic Mathematics Education (RME) approach in enhancement, and achievement of Mathematical Creative Thinking Ability (MCTA) in flat side of solid figure of  Pyramid dan Prism learning of Junior High School students’ would improve students’ mathematical creative thinking in terms of students' minimum criteria of mastery learning (KKM). The method used was classroom action research with planning, implementation of the action, evaluation, and reflection design in 3 cycle. The subject of this research was 8th-A graders in SMP BPK Penabur Holis Bandung. The instrument used an essay test on MCTA, observation sheets, and interview sheets. Data analysis was done quantitatively, in quality and descriptive basis. The results showed that: (1) Students ' learning through RME was better than their previous grades, (2) MCTA of students whose study used the RME approach enhancement 32.28% from cycle I to cycle II and 6.45% from cycle II to cycle III, (3) Students' MCTA in each indicator have equalization